Effect of 20% Water Content on the Properties (Cetane Number, Rheology and Stability) of Emulsion Fuel in Comparison to the Commercial Diesel - Issaka, Souleyman A.; Nour, A. H.; R. M., Yunus (IJCR, 2015)
This paper is aimed to investigate the change in the properties of the diesel when emulsified with water and become emulsion (emulsion fuel). The properties of 20 were determined based on periodic measurement. The experimental test for duration of one month. The emulsion was assessed by measuring its viscosity, cetane number and water resolution as function of time. However, results showed that, addition of 20% water in the commercial diesel had high as 9 mpa.s in the emulsion fuel, while aging had very minor effect on viscosity. Furthermore, the cetane number also increased from 56.9 in the original commercial diesel With regard to water resolution, 7% water and 10% oil layers were resolved, but quantitatively, there was a water rich mixture settled at the bottom and an oil rich mixture at the top. This study proved that aging have very ma ambiguous and not easy to determine since there were no clear boundaries between layers, and the whole sample turns to gray color with time instead of milky white initially.